Female Corporate Leadership in Latin America and the Caribbean Region: Representation and Firm-Level Outcomes - Luca Flabbi; Claudia Piras; Scott Abrahams (Inter-American Development Bank (IDB), 2016)
This paper collects an original database of publicly listed companies to determine prevailing gender ratios among board members and executives in Latin America and the Caribbean region (LAC). Women are as under-represented in LAC as in the United States, but much less so in the Caribbean. It is then estimated whether companies with women board members are more likely to appoint women executives. This is the case in LAC, but the results are driven strongly by Caribbean companies. The paper finally estimates whether measures of female leadership at the firm are correlated with company performance, finding this to be the case only for board membership and only when the proportion of women on the board is greater than 30 percent. Again composition effects are important, with average results driven by Caribbean and Southern Cone companies. Overall, it is concluded that the LAC regions empirical regularities in under-representation of women in firm leadership positions are very similar to those found for high-income countries in Europe and North America.
hdl:11319/7386
Keywords: J16; J7; M12; M5; 330; Executive gender; Women board members; Gender quotas; Glass ceiling; Glass cliff; Gender gap